Avanços e dilemas da experiência regional brasileira: o caso da Agência de Desenvolvimento do Grande ABC - Souza, Daniela Coimbra de (2003)
The history of the Agency of Economic Development of Great ABC is described in it's formation and development as an institution of regional administration which includes public entities - the seven city administrations - and institutions of civil society: employers', employee's and academic representatives. The questions discussed are the impacts of the federalism and the lack of politics to solve common problems of the different governmental units in a rnetropolitan region, discouraging the cooperation between the federative entities in these regions. The central point of the analysis is that, in spite of theses obstac1es, there was developed an experience, unique in Brazil, of inter- and intragovernrnental cooperation with support of the local society, which, however, presents limitations. The process of constructing a dialogue and unity between different participants is clarified with its phases, participants, institutions and conflicts and its impacts on the development of the Agency.